Political Economy of Forest Tenure Reform Implementation in Nepal: Evolution, Contestation, Outcomes and Challenges - Banjade, Mani Ram; Paudel, Naya S; Mwangi, Esther (Journal of Forest and Livelihood, 2017)
Not available.